2012
DOI: 10.5142/jgr.2012.36.4.425
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ginsenoside and Phenolic Ingredient Contents in Hydroponically-cultivated Ginseng Leaves, Fruits, and Roots

Abstract: In this study, hydroponically-cultivated ginseng leaves, fruits, and roots were respectively extracted with ethanol. The contents of 12 ginsenosides and three phenolics in the extracts were quantitatively analyzed and the free radical scavenging activities were measured and compared. Hydroponically-cultivated ginseng leaves contained higher levels of gensenosides (Rg1, Rg2+Rh1, Rd, and Rg3) and p-coumaric acid than the other parts of the ginseng plants. The 2,2’-azino-di-(3-ethylbenzothiazoline)-6-sulfonic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 8 publications
(5 reference statements)
0
31
1
Order By: Relevance
“…It is presumed that this approach is most suitable and effective for good manufacturing practices [53,54]. In particular, soilless cultivation of ginseng in hydroponics and aeroponics cultures is most appropriate due to many reasons [55,56], including the fact that this method is safe and free of pesticides and agrochemicals [57,58]. Parameters including nutrient-solution composition, pH, aeration, temperature, light, and numerous stressful factors are crucial not only for optimal plant growth and development, but also for the increased biosynthesis of pharmacologically active secondary plant metabolites that play important roles in plant defense response and survival [55,56,59].…”
Section: Ginsenosides Hrg80 (Mg/g *) Arkopharma (Mg/g) Placebomentioning
confidence: 99%
See 1 more Smart Citation
“…It is presumed that this approach is most suitable and effective for good manufacturing practices [53,54]. In particular, soilless cultivation of ginseng in hydroponics and aeroponics cultures is most appropriate due to many reasons [55,56], including the fact that this method is safe and free of pesticides and agrochemicals [57,58]. Parameters including nutrient-solution composition, pH, aeration, temperature, light, and numerous stressful factors are crucial not only for optimal plant growth and development, but also for the increased biosynthesis of pharmacologically active secondary plant metabolites that play important roles in plant defense response and survival [55,56,59].…”
Section: Ginsenosides Hrg80 (Mg/g *) Arkopharma (Mg/g) Placebomentioning
confidence: 99%
“…Parameters including nutrient-solution composition, pH, aeration, temperature, light, and numerous stressful factors are crucial not only for optimal plant growth and development, but also for the increased biosynthesis of pharmacologically active secondary plant metabolites that play important roles in plant defense response and survival [55,56,59]. Choi et al [55] cultivated P. ginseng in hydroponics and observed higher ginsenoside and phenolic content in its leaves.…”
Section: Ginsenosides Hrg80 (Mg/g *) Arkopharma (Mg/g) Placebomentioning
confidence: 99%
“…HPLC analysis was performed according to Choi, Cho et al (2012). The contents of kaempferol, quercetin, quercetin-3-rutinoside, and ellagic acid were analyzed by a HPLC system (Jasco, Tokyo, Japan).…”
Section: Determination Of the Phenolic Compound Contentsmentioning
confidence: 99%
“…Recently, based on the information of health beneficial effects of bokbunja, the growth area and the harvest quantity in South Korea have rapidly increased resulting in various bokbunja products, such as juices and concentrates, rice cakes, vinegar, and dietary supplements. Several studies have shown that bokbunja fruit and wine are positively related with various physiological functions, including antioxidative , anti-inflammatory (Lim, Hwang, & Shin, 2012;Yang et al, 2007), anticancer (Jung et al, 2009), anti-high cholesterol (Lee et al, 2015), and prevention of the memory impairment (Choi, Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Ginseng is a kind of traditional Chinese medicine, ginseng polysaccharides which because of its anti-tumor, anti-oxidation, hypoglycemic, and many other activities was widespread concern in recent years [3] [4]. The ginseng root requires 6 -7 years to harvest, while ginseng leaves can be harvested annually; recent studies have shown that there was the same active ingredient in the ginseng and ginseng leaves, such as fatty acids, alkaloids, polysaccharides, sesquiterpenes, ginsenosides and so on [5] [6]. But the ginseng leaves activities especially the anticancer activity have not been reported.…”
Section: Introductionmentioning
confidence: 99%